ANALISIS HUBUNGAN PANJANG BERAT IKAN KERAPU (Epinephelus sp) YANG DIDARATKAN DI KALIADEM DAN PASAR IKAN MUARA ANGKE, JAKARTA - Rizky Janatul Magwa; Ester Restiana Endang Gelis; Lauura Hermala Yunita; Yoppie Wulanda; Septy Heltria; Farhan ramdhani (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2023)
Grouper (Epinephelus Sp.) is an economically important fish that lives in coral reefs and is widely consumed by the public. It is necessary to analyze the relationship between the length and weight of fish at the Kaliadem fish landing site and Muara Angke market. This research aims to determine the relationship between length and weight of fish. Data on the length and weight of the fish were taken from a sample of 20 grouper fish sold at the two locations. This Research was carried out in April 2018. This study used survey method, observation of grouper morphology. The analysis used in this research uses multiple linear regression analysis. The research showed that grouper fish had a length range of 128 mm – 169 mm and a weight range of 31 g – 65 g with an average length of 144.5 mm and an average weight of 42.75. The results of linear regression on the relationship between the length and weight of grouper fish samples produced a regression equation Y = 2.7424x – 9.8972 with a value of b = 2.74 and a coefficient of determination of 0.9281. significant b < 3 means the allomatric growth pattern is negative and 98.97% of changes in fish weight occur due to an increase in fish length, while 1.03% is caused by other factors. It can be concluded that length growth is faster than weight gain in grouper fish. The condition factor value of the grouper this research had a Fulton condition factor value (K) ranging from 2.95 to 3.17 and a relative weight (Wr) ranging from 86.50 to 106.41 with an average Wr value of 100.31.